Synthesis, Characterization, and Evaluation of the Antimicrobial and Anticancer Activities of Zinc Oxide and Aluminum-Doped Zinc Oxide Nanocomposites - Muhammad Asif; Muhammad Fakhar-; Muhammad Tahir; Farah Jamil; Hassan Sardar; Javed Rehman; Kholood A. Dahlous (MDPI AG, 2024)
In this research, we developed undoped and aluminum-doped zinc oxide for antimicrobial and anticancer activities. This study focuses on the synthesis, characterization, and biological activities of zinc oxide nanoparticles (ZnO NPs) and aluminum-doped zinc oxide nanocomposites (Zn1−xAlxO NCs) at varying concentrations (x = 0, 0.25, 0.5, and 0.75 wt%) using the coprecipitation method. Various characterization techniques such as XRD, UV-Vis, FTIR, EDX, and SEM were performed to analyze the crystal structure, optical properties, functional group identification, elemental composition, and surface morphology. The antimicrobial activity test showed that Zn0.75Al0.25O NCs exhibited the strongest inhibition zone against Bacillus cereus compared to Staphylococcus aureus > Pasteurella multocida > Escherichia coli. Moreover, the cytotoxicity and cell viability of liver cancer (HepG-2), breast cancer (MCF-7), ovarian cancer (SKOV3), and normal liver cell lines) were evaluated using the MTT assay, demonstrating that Zn0.75Al0.25O NCs not only enhance cell destruction but also show low cytotoxicity and high biocompatibility at low concentrations. These results suggest that Zn0.75Al0.25O NCs could be a promising candidate for in vivo anticancer applications and should be further investigated.